Mercury concentrations in Alaska Pacific halibut muscle relative to stable isotopes of C and N and other biological variables. Issue 1 (15th December 2016) - Bentzen, Rebecca; Castellini, J. Margaret; Gerlach, Robert; Dykstra, Claude; O'Hara, Todd
Abstract: Total mercury concentrations ([THg]), δ 15 N and δ 13 C values were determined in muscle of 693 Pacific halibut caught in International Pacific Halibut Commission setline surveys in Alaska (2002 − 2011). Project goals were to evaluate whether 1) δ 15 N and δ 13 C varied with region, age, sex and length of halibut, and 2) muscle [THg] varied with δ 15 N and δ 13 C (feeding ecology) while accounting for sex, length, and region. Variation in [THg] was explained, in part, by halibut feeding ecology as [THg] increased with trophic position (increasing δ 15 N). Halibut from the western Aleutian Island region were the exception, with overall lower δ 15 N values and significantly higher [THg] than halibut from other Alaskan waters. This [THg] pattern has been observed in other Aleutian biota, possibly the result of northeasterly atmospheric movement of mercury emissions from Asia and/or other local sources and processes. The significantly lower δ 15 N values for these halibut warrants further investigation of halibut prey. Highlights: Mercury, δ 15 N, and δ 13 C were determined in muscle of 693 Pacific halibut in Alaska. Variation in muscle mercury level was explained, in part, by halibut feeding ecology. Muscle mercury concentration generally increased with relative trophic position (δ 15 N). Western Aleutian halibut had lower δ 15 N and higher mercury than other regions. Assessment of mercury and trophic relationships accounted for sex, size, and region.